Experimental studies on photocatalytic reduction of CO2 using AgBr decorated g-C3N4 composite in TEA mediated system. (December 2017) - Murugesan, Pramila; Narayanan, Sheeba; Manickam, Matheswaran
Graphical abstract: Highlights: Cubic crystal of AgBr decorated g-C3 N4 was fabricated by modified deposition-precipitation method. g-C3 N4 /AgBr composite exhibits enhanced photocatalytic activity for reduction of CO2 to methane and acetone in aqueous medium. Effect of reductants, pH and catalyst dosage were investigated in detail. Mechanism for CO2 reduction over g-C3 N4 /AgBr composite was proposed. Abstract: Graphitic carbon nitride modified with silver bromide (AgBr/g-C3 N4 ) composite was prepared by modified deposition-precipitation method. The phase structure, optical property, thermo stability, morphological structure, elemental composition, surface area and surface charge of AgBr/g-C3 N4 composite were characterized using various analytical techniques. XRD spectrum for AgBr/g-C3 N4 composite reveals that cubic phase of AgBr crystal is deposited on the surface of g-C3 N4 . The AgBr/g-C3 N4 composite showed slightly enhanced visible light active, which was confirmed from UV- vis absorbance spectra. The BET surface area of pure AgBr, g-C3 N4 and AgBr/g-C3 N4 composite were 4.802 m 2 /g, 12.74 m 2 /g and 15.52 m 2 /g respectively. Subsequently, the photocatalytic activity of AgBr/g-C3 N4 composite was evaluated towards the reduction of carbon dioxide (CO2 ) under UV light irradiation. The effects of reductants, pH, catalyst dosage and stability were also studied. The maximum production yield of methane (61.52 μmol/g), hydrogen (58.89 μmol/g) and acetone (3.32 μmol/g) in triethanolamine (TEA) medium was observed at pH 9 and catalyst dosage 3 g/L. It was inferred that AgBr/g-C3 N4 composite has the highest photocatalytic activity than that of pure g-C3 N4 .